CHEMICAL ACTIVATION OF ALPACA OOCYTES VITRIFIED AFTER IN VITRO MATURATION - Ruiz B., Jaime (2011)
The aim of this study was to evaluate the viability of vitrified/thawed alpaca oocytesafter in vitro maturation. Alpaca oocytes were retrieved from ovaries obtained in theslaughterhouse of Huancavelica, Peru and matured in vitro for 24-25 h in a modularchamber with 5% O2, 5% CO2 and 90% N2 in TCM-199 medium supplemented with sodiumpyruvate, HEPES, gentamycin sulphate, FSH, estradiol 17-?and fetal calf serum. Then,oocytes were fully denuded of cumulus cells with 0.1% hyaluronidase and assigned tothree treatments: T1 (n=107), oocytes exposed to cryoprotectans and vitrified; T2 (n=121),oocytes exposed to cryoprotectans without vitrification; and T3 (n=232), control groupof oocytes not exposed to vitrification solutions. Alpaca oocytes were vitrified inmicrodrops on a precooled aluminum foil floating in liquid nitrogen, using an equilibriumsolution with 4% ethylene glycol and a vitrification solution with 35% ethylene glycol,5% polyvinyl-pyrrolidone and 0.4 M trehalose. The vitrified microdrops were stored inliquid nitrogen and were thawed 1-4 d later. All oocytes were cultured on SOF-HEPESwith 5 ?mM Ca ionomycin by 4 min at room temperature followed by 3 h incubation in 6-DMAP at 38.5 ºC in a 5% O2, 5% CO2 and 90% N2 in humidified atmosphere. Subsequently,were cultivated on mSOF medium during 8 days. The rates of oocytes survival were 58.4,68.7 and 97.3% in T1, T2 and T2 respectively. The rates of cleavage were 39.9, 49.5 and62.3% and rates of development to blastocysts were 0, 0 and 9.2% in T1, T2 and T3respectively. The results showed that alpaca oocytes were morphologically andphysiologically viable after vitrification by solid surface method.